KEANEKARAGAMAN JENIS NYAMUK Anopheles DI DAERAH DENGAN ATAU TANPA KEBUN SALAK DI KABUPATEN BANJARNEGARA - Dyah Widiastuti; Bambang Yunianto; Bina Ikawati (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2006)
Anopheles has been known as vectors of malaria and filaria. A research which was aimed to evaluate the diversity of Anopheles mosquitoes at Salak and Non Salak Areas was conducted. This Research located in Banjarnegara Regency which lay in a mountainous in the middle of Central Java (7'12